Renal Cell Carcinoma (RCC) Tumors Display Large Expansion of Double Positive (DP) CD4+CD8+ T Cells With Expression of Exhaustion Markers - Menard, Laurence C.; Fischer, Paul; Kakrecha, Bijal; Linsley, Peter S.; Wambre, Erik; Liu, Maochang C.; Rust, Blake J.; Lee, Deborah; Penhallow, Becky; Manjarrez Orduno, Nataly; Nadler, Steven G. (Frontiers in Immunology, 2018)
Checkpoint inhibitors target the inhibitory receptors expressed by tumor-infiltrating T cells in order to reinvigorate an anti-tumor immune response. Therefore, understanding T cell composition and phenotype in human tumors is crucial. We analyzed by flow cytometry tumor-infiltrating lymphocytes (TILs) from two independent cohorts of patients with different cancer types, including RCC, lung and colon cancer. In healthy donors, peripheral T cells are usually either CD4+ or CD8+ with a small percentage of CD4+ CD8+ DP cells (<5%). Compared to several other cancer types, including lung and colorectal cancers, TILs from about a third of RCC patients showed an increased proportion of DP CD4+CD8+ T cells (>5%, reaching 30-50% of T cells in some patients). These DP T cells have an effector memory phenotype and express CD38, 4-1BB and HLA-DR, suggesting antigen-driven expansion. In fact, TCR sequencing analysis revealed a high degree of clonality in DP T cells. Additionally, there were high levels of PD-1 and TIM-3 expression on DP T cells, which correlated with higher expression of PD-1 and TIM-3 in conventional single positive CD8 T cells from the same patients. These results suggest that DP T cells could be dysfunctional tumor-specific T cells with the potential to be reactivated by checkpoint inhibitors.